INFLUENCE OF AGGREGATE GRADING,ON THE CHARACTERISTICS OF ASPHALT CONCRETE BINDER COURS - T.Idaman
INFLUENCE OF AGGREGATE GRADING ON THE CHARACTERISTICS OF ASPHALT CONCRETE BINDER COURSE, T. Idaman, 1999, Program Magister Sistem dan Teknik Jalan Raya, Program Pascasarjana, Institut Teknologi Bandung. To facilitate construction of the asphalt layers of a pavement, deviations are permitted from the aggregate grading approved for the Job-Mix formula. Permissible deviations or tolerances are specified for different ranges in aggregate particle size but the extent to which these can influence mix performance is not normally assessed. This thesis describes a laboratory investigation of the effect of such deviations on the composition and strength characteristics of a binder course mix. The control grading was the middle grading or median of the specified grading band. Aggregate graded to the middle grading plus and minus the permitted tolerances (designated the Maximum and Minimum Tolerance gradings, respectively) were also investigated as were four gradings within the limits defined by the upper and lower tolerances. Optimum bitumen contents were determined for the seven gradings by Marshall analysis and all mixes complied with Bina Marga Marshall criteria. Mixes at optimum bitumen contents were evaluated for durability in Marshall immersion test and for resistance to permanent deformation in the wheel tracking test. The amount of aggregate passing, or retained on, the 2.38 mm sieve appears to have a primary influence on mix composition and performance. Mixes with a relatively high percentage of material passing the 2.38 mm sieve (47.5 %) require most bitumen and have highest durability but have inferior strength characteristics. Mixes with a relatively low percentage of material passing the 2.38 mm sieve (37.5 to 38.5 %) require least bitumen and have superior strength characteristics. The durability of these mix, albeit lower then the more fine-graded mixes, is still satisfactory. Mixes with an intermediate amount retained on the 2.38 mm sieve (42.5 %), including the Middle grading, have composition and strength characteristics around the middle of the range observed. The data suggest the fine-graded mixes, as indicated by the percentage passing or retained on the 2.38 mm sieve should be avoided when possible and that the most satisfactory design is likely to be achieved when the percentage passing (retained on) the 2.38 mm sieve is in the range 38.5 to 42.5 % (61.5 to 57.5 %)